Hypofractionated image-guided radiotherapy with 70 Gy in 28 fractions for prostate cancer confined to the pelvis: a single institute experience in Taiwan - Hui-Lei Mu; Mau-Shin Chi; Hui-Ling Ko; Guang-Dar Juang; Thomas I-Sheng Hwang; Kwan-Hwa Chi; Kai-Lin Yang (BMC Urology)
Abstract Background The incidence of prostate cancer is increasing in Asian countries. Although moderately hypofractionated radiotherapy is not inferior to conventional fractionated radiation according to the updated guidelines, data regarding its efficacy and safety in Taiwan are currently lacking. The aim of this study was to investigate the outcomes of prostate cancer patients treated with hypofractionated image-guided radiotherapy at a single institution in Taiwan. Methods We retrospectively included patients with prostate cancer across all risk groups who were treated with hypofractionated image-guided radiotherapy 70 Gy (Gy) in 28 fractions (at 2.5 Gy/fraction) between 2007 and 2022. We analyzed treatment efficacy by assessing overall survival, prostate cancer-specific survival, event-free survival, biochemical failure, locoregional recurrence, and distant metastasis. The safety of the treatment was evaluated through acute and late gastrointestinal (GI) and genitourinary (GU) toxicity grading based on the Radiation Therapy Oncology Group criteria. Event-free survival, overall survival, prostate cancer-specific survival, biochemical failure, locoregional recurrence, and distant metastasis were evaluated using the Kaplan–Meier method. Results We identified 150 consecutive men with prostate cancer: 12.7% were at low risk, 32.7% were at intermediate risk, 44.6% were at high risk, and 10% had N1 disease. The median follow-up time was 68.9 months (range: 2.3–172 months). The 5-year overall survival rate was 91.7% for the entire cohort, with rates of 100%, 94.3%, 93.3% and 71.1% for the low-risk, intermediate-risk, high-risk, and N1-disease groups, respectively (p < 0.001). The 5-year event-free survival rate for all patients was 75.8%. Among the risk groups, the 5-year event-free survival rates were 100%, 86.3%, 68.3% and 52.5% for the low-risk, intermediate-risk, high-risk, and N1 disease groups, respectively (p < 0.001). Grade ≥ 2 late GI toxicity was rare (0.7%), and grade ≥ 2 late GU toxicity was observed in 9.3% of the patients. Conclusions Hypofractionated image-guided radiotherapy, delivering 70 Gy at 2.5 Gy per fraction, is both effective and safe for Taiwanese patients with prostate cancer across all risk groups, consistent with findings from existing large randomized trials. Therefore, as a solution to enhance patient convenience, hypofractionated radiotherapy is a reasonable option for the definitive treatment of prostate cancer. Trial registration Not applicable.